Effectivity of Uniform Multidrug Therapy on the Success of Paucibacillary and Multibacillary Leprosy Treatment - Prayogi Miura Susanto; Prima Kartika Esti; Eka Komarasari (Nepal Journal of Dermatology, Venereology & Leprology)
Leprosy is a chronic infectious disease caused by Mycobacterium leprae (M. leprae) that involves the integumentary and peripheral nervous system, causing neuropathy, deformity, and disability. Early detection and appropriate treatment are the ways to break the chain of transmission and prevent disability in leprosy patients. The first line of treatment for leprosy is the standard Multidrug Therapy (MDT) regiment consisting of rifampicin, dapsone, and clofazimine. Standard MDT treatment is given based on the leprosy classification of paucibacillary (PB) and multibacillary (MB). The utilization of the standard MDT regiment has some limitations, particularly where there is a limited supporting test facility, causing difficulty in determining the leprosy classification accurately. An alternative regiment proposed to substitute the standard MDT is the Uniform-MDT (U-MDT). Several studies have been conducted on the use of U-MDT and have produced promising results for the treatment of PB and MB leprosy.